Careers guidance provisions and progression to post-16 education: An empirical analysis for Wales - Davies, Rhys; Yunus, Suhaer; Huxley, Katy (International Journal of Population Data Science, 2019)
Careers guidance is widely regarded as important in supporting young people in making appropriate decisions following school. However, there is very little empirical evidence as to its effectiveness. This paper examines whether the services provided by Careers Wales have encouraged progression to post-compulsory education in Wales. The paper uses administrative education data for 2 cohorts of school pupils who completed their final year of compulsory education in Wales 2012/13 and 2013/14. Through linkage to individual level client records held by Careers Wales, those pupils who had received careers guidance during their final 2 years of school are identified. Further linkage to records regarding participation in either school based sixth-forms or colleges of Further Education provides a complete picture of participation in post-compulsory education among Welsh pupils and how rates of transition vary among different groups of pupils, including whether or not pupils had had some form of contact with Careers Wales. Multivariate statistical analysis was undertaken to examine whether or not, after controlling for other characteristics, accessing the services of Careers Wales was associated with the likelihood of attending post-compulsory education. The results based on multivariate logistic regression analysis reveal that receiving careers guidance through the medium of group sessions increases the likelihood of overall participation in post-compulsory education. The effect of this is enhanced when pupils also received a one to once careers interview during the last 2 years of school. In general, careers interventions are associated with a reduced likelihood of attendance at Sixth Form but encourages student transition to Further Education. The study offers important insights for policy makers and career practitioners in terms of the contributions of careers guidance in supporting post-16 educational landscape in Wales.